Evaluación de la eficiencia del quemado de ladrillo de arcilla con cascarilla de arroz y la generación de residuos sólidos en hornos cerrados - Pezo Fachín, Milagros (2013)
At present one comes observing that the use of the rice husk represents an energetic alternative for the volumes of production that generate the rice mills what guarantees the sustainability of the resource as for availability of raw material. Through this research work was able to determine the efficiency of the rice husks for the burned clay brick, for which 05 companies were chosen that brick makers have closed furnaces and used in a 100% rice husks located in Rioja and Moyobamba province, the evaluation was carried out for six (06) months with a frequency of one (01) burning per month, in total there were six (06) consecutive assessments, registering information as quantity of rice husk used by burning, quantity in % and kg, ashes generation, broken bricks, raw bricks, between other own characteristics of the system of burning and ovens; in a parallel manner data was recorded for the same variables applied to the furnaces that burn with rice husks, which burned with wood and coal. In order to establish comparison and perform the technical and economic comparisons. Since result of the evaluated with the use of rice husk generates an average of 33.6 units of torn and raw brick for thousands of burnt brick that represents the 3.36 % for the lack of oxygenation of the husk at the time of combustion; wood burning with an average of 1800 units and burning coal ore with a total of 12.80 units ofbroken bricksraw /thousand brick burned; which demonstrates to us that the rice husks in conditions as is being done the burning of the brick does not represent efficiency compared to other altemative sources such as firewood and coal. In respect to the ashes generation, the closed fumaces that use rice husks have generated a total of 192.73 kg of ash per thousand of burned brick, this shows us that the use of this energy source generates the greatest amount of ash by increasing the generation of particulate material during and after the burning process, the same that may affect the workers health and population of the area, in comparison with the furnaces that bum wood in 25.00 kg per thousand and mineral coal in 5 kg of ash by thousands of bumed brick. Key words: energetic altemative, rice husks.